Contemporary Governance Challenges in the Horn of Africa - Fombad, Charles Manga; Fiseha, Assefa; Steytler, Nico (Taylor & Francis, 2023)
This book argues that a leading cause of the political instability in the Horn of Africa is a crisis of governance, caused by extreme centralization of power, weak institutions, and the failure to institutionalise the responsible use of authority. In recent years, many attempts have been made to resolve the ongoing conflicts in Somalia and South Sudan, but problems remain, and in 2019 the instability spread to Ethiopia. This book critically examines how many of the governance problems in the region can be addressed through institutional design. The central argument is that an inclusive system of governance through federalism, devolution, and inclusive political institutions as well as ensuring the institutionalization of power through strengthening the rule of law has the potential to make governments more accountable, inclusive, and be able to deliver critical services. Such systems ensure relative stability and peace and reduce the risks of state fragmentation - a major concern in the region. Demonstrating that the threats of further fragmentation and conflict due to the crisis of governance are likely to continue unless serious steps are taken to deal with the situation, the book will be an important read for researchers and policy makers with an interest in peacemaking, politics, constitutional law, and federalism in the region.